Permittivity of Plasma in Random Fields of Moderate Intensity - Zasenko, V.I.; Zagorodny, A.G.; Weiland, J. (Ukrainian Journal of Physics, 2022)
The permittivity of plasma in the electric field of random waves of moderate intensity is given in terms of the particle transition probability between two points of the phase space. The transition probability was found as an approximate solution of the Fokker–Planck equation. Validity of this analytical approximation was verified by the direct simulation of the particle diffusion in a field of random waves.